Pelaksanaan Hak dan Kewajiban dalam Praktik Nikah Gantung: Studi Kasus di Desa Pekan Tanjung Beringin, Kabupaten Serdang Bedagai (Tinjauan Kompilasi Hukum Islam) - Uswatun Hasanah; Zulkifli Nas (Al-fiqh, 2026)
This study examines the fulfillment of marital obligations and rights in the practice of nikah gantung in Pekan Tanjung Beringin Village, Serdang Bedagai Regency, as viewed through the lens of the Compilation of Islamic Law. Issues arise because, in the practice of nikah gantung, the fulfillment of marital rights and obligations is postponed indefinitely. This situation has sparked debate within Islamic law regarding the compatibility of the nikah gantung practice with the purposes of marriage, particularly concerning the fulfillment of financial support, protection, and cohabitation following the marriage contract. This study aims to examine the concept of nikah gantung according to Islam and the Compilation of Islamic Law (KHI), the factors underlying the practice, and an analysis of the fulfillment of the rights and obligations of husbands and wives. The research method used was qualitative research with an empirical-juridical approach through interviews and documentation. The results show that the practice of suspended marriage is legally valid under Islam if the pillars and conditions of marriage are fulfilled; however, in practice, the husband’s obligations toward his wife are often not fully met particularly regarding financial support and housing thereby potentially creating inconsistencies with the provisions of the Compilation of Islamic Law.